ANALISIS PERSEPSI MAHASISWA TERHADAP KUALITAS SARANA DAN PRASARANA PEMBELAJARAN - Kitia Dwi Yuni; Sasta Seftia; Anisa Puspa Sary; Miranti; Afriantoni (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study was motivated by the importance of the quality of learning facilities and infrastructure in supporting effective and optimal learning processes in higher education. The study aimed to analyze students’ perceptions of the quality of learning facilities and infrastructure available at the university. This research employed a quantitative approach using questionnaires distributed to students as the data collection technique. The research instrument consisted of closed-ended questionnaires developed based on indicators of learning facilities and infrastructure quality. The collected data were analyzed using descriptive statistical techniques to determine the level of student satisfaction and assessment of the available facilities. The findings revealed that students generally had positive perceptions regarding the quality of learning facilities and infrastructure. However, several aspects still require improvement, including the completeness of facilities, the comfort of learning spaces, and access to learning support technology. This study contributes to the development of educational service quality through continuous improvement of facilities and infrastructure to support the success of the learning process in higher education.